Effect of prehabilitation in gastro-oesophageal adenocarcinoma: study protocol of a multicentric, randomised, control trial—the PREHAB study. Issue 12 (7th December 2016) - Le Roy, Bertrand; Pereira, Bruno; Bouteloup, Corinne; Costes, Frédéric; Richard, Ruddy; Selvy, Marie; Pétorin, Caroline; Gagnière, Johan; Futier, Emmanuel; Slim, Karem; Meunier, Bernard; Mabrut, Jean-Yves; et al.
Abstract : Introduction: Perioperative chemotherapy is the gold standard treatment of the resectable gastro-oesophageal adenocarcinoma. However, 70% of patients cannot receive the complete sequence because of a postoperative complication or a decrease in functional and nutritional reserves. Recently, a new concept appeared in digestive surgery: prehabilitation. This interventional process consists of patient preparation, between surgical consultation and surgery, and is based on 3 components: (1) physical management, (2) nutritional care and (3) psychological care. Prehabilitation should decrease postoperative complications and improve nutritional and physical status during the preoperative and postoperative periods. Therefore, it is becoming essential to evaluate the effect of prehabilitation, compared to conventional care, on the percentage of patients reaching the complete oncological treatment. Methods and analysis: The PREHAB trial aimed to evaluate the efficacy of prehabilitation compared to conventional care, in patients with gastro-oesophageal cancer with perioperative chemotherapy. This trial is a prospective, randomised, controlled, open-blind and interventional study in 4 centres. Patients (n=60 per group) will be randomly assigned for management with either prehabilitation or conventional care. The primary outcome is the percentage of patients reaching the complete oncological treatment decided in a multidisciplinary tumour board. The secondary outcomes are the postoperative morbidity, disease-free survival, overall survival, feasibility of the protocol, length of stay, variation of the functional reserve after the preoperative chemotherapy (defined by the VO2peak, ventilatory threshold and 6-min walk test), preoperative and postoperative nutritional status, preoperative anxiety, quality of life, 30-day and 90-day mortality and cumulative dose of cytotoxic treatment received. Ethics and dissemination: The study was approved by an independent medical ethics committee (IRB00008526, CPP Sud-Est VI, Clermont-Ferrand, France) and by the competent French authority (ANSM, Saint Denis, France) and registered on Clinicaltrial.gov . The results will be disseminated in a peer-reviewed journal. Trial registration number: NCT02780921.